Rome remembers fascism: the monument to the Fosse Ardeatine massacre as immersive historical experience. Issue 1 (2nd January 2017) - Marcello, Flavia
Abstract: One day in the early 2000s, while driving along Rome's Via Ardeatina I saw a street sign: Largo Martiri delle Fosse Ardeatine . It piqued my curiosity so I parked the car to find out more about these martyrs and these fosse ? About an hour later I was back in my car weeping. I had gone to an underworld and back again, through an idyllic park, that housed a site of shootings, burials, exhumations and re-burials. At the Monument to the Fosse Ardeatine Massacre (1949) I had retraced the steps of victims, perpetrators and mourning families through an immersive experience of place. As a person I would never be the same again. As a historian, I feel I can now write about it. Like many war memorials, this monument embodies shared narratives and memories about war and identity, resistance and cruelty. While it does not actually tell the big story, it has the power to spark multiple stories, memories, or emotional responses that are both individual and collective. The Fosse re-presents accounts of what happened in Italy under Nazi occupation, it harbours the histories of those who did not survive and keeps them as signposts for us, for those who did. It is a guardian of the many narratives of its daily visitors. It is a marker that divides Italy's fascist and anti-fascist pasts, both historically and architecturally. Although the order from Hitler for the reprisal killing at the Fosse Ardeatine was carried out many years ago, the existence of the monument continues to mediate the past and anchor it in the present.